COMPARATIVE ANALYSIS OF FOREIGN EXPERIENCES IN THE DEVELOPMENT OF PROFESSIONAL STANDARDS OF TEACHERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides a comparative analysis of the professional standards of teachers in practice in foreign countries, the approaches to their creation, content and expected results, as well as best practices.